2002
DOI: 10.21000/jasmr02010241
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Wildlife Habitat At The Buckskin Mine

Abstract: The Surface Mining Control and Reclamation Act and supporting regulations contain numerous requirements for the reclamation of wildlife habitat. However, these requirements are often contradicted by other requirements. Historically, regulatory agencies have tended to place more emphasis on those requirements that act to impede the reclamation of wildlife habitat then they have on those requirements that restore and/or enhance wildlife habitat. Wildlife habitat is a principal postmining land use over most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Following the literature review, it became apparent that the active factors of all design approaches, regardless of their definitions, included humans or nature or both (mixed). Studies made in this regard revealed a total of 62 nature or human-oriented uses for topography, water, and vegetation as far as the uses of landscaping elements are concerned (Table 3) (Arbogast et al, 2000;Arnegger, Woltering, & Job, 2010;Benson, 2002;Coghlan & Buckley, 2013;Görcelio glu, 2002;Kivinen, 2017;Lintukangas & Suihkonen, 2009;Lintukangas, Suihkonen, Salomäki, & Selonen, 2012;Mborah et al, 2016;Salminen, 2007;Strasdas, 2006;Wang, 2013).…”
Section: Findings Regarding Design and Usage Scenariosmentioning
confidence: 99%
“…Following the literature review, it became apparent that the active factors of all design approaches, regardless of their definitions, included humans or nature or both (mixed). Studies made in this regard revealed a total of 62 nature or human-oriented uses for topography, water, and vegetation as far as the uses of landscaping elements are concerned (Table 3) (Arbogast et al, 2000;Arnegger, Woltering, & Job, 2010;Benson, 2002;Coghlan & Buckley, 2013;Görcelio glu, 2002;Kivinen, 2017;Lintukangas & Suihkonen, 2009;Lintukangas, Suihkonen, Salomäki, & Selonen, 2012;Mborah et al, 2016;Salminen, 2007;Strasdas, 2006;Wang, 2013).…”
Section: Findings Regarding Design and Usage Scenariosmentioning
confidence: 99%